The Role of Leadership, Work Discipline, and Compensation in the Performance of the Sales Team at PT Indosat Ooredoo Sales Area Palembang - Saputri, Selfi; Handayani, Susi; Veronica, Meilin (SIMAK, 2025)
This study aims to analyze the impact of leadership, work discipline, and compensation on team performance at PT Indosat Ooredoo Sales Area Palembang. The research uses a quantitative approach with a survey method, involving 92 respondents who are employees of the company. Data were collected through questionnaires and processed using multiple linear regression analysis to test the impact of the three independent variables on the dependent variable, which is team performance. The results show that leadership and work discipline have a significant impact on team performance, while compensation does not show a significant effect. The results of the simultaneous test concluded that the independent variables simultaneously, namely Leadership, Work Discipline, and Compensation, had a significant influence on the dependent variable, namely Team Performance. These findings provide insights for the company to enhance team performance by improving leadership and strengthening work discipline. This study also suggests the importance of improving compensation strategies to increase employee motivation and performance.